The German experience in implementation of blended learning strategies - Osadcha, Kateryna (Educological discourse, 2022)
In the article, based on the analysis of the scientific works of German scientists from 2006 to 2021, the conclusion is made about the incentives for the spread of blended education in Germany: unacceptable distances to the nearest educational institutions; special religious and language needs that local educational institutions are unable or unwilling to meet; individuality of learning; avoiding social problems resulting from face-to-face communication; consolidation of educational materials and increase of hours for independent study. The strategies of blended learning at higher education institutions are highlighted: the strategy of preliminary development of materials for face-to-face learning and subsequent development of materials for electronic learning, taking into account the individual preferences of students (J. Dammeier, S. Merten); the combination of equal volume of theoretical and practical materials in a clear, implemented and measurable approach with the aim of purposeful development of practical knowledge in face-to-face and electronic learning as parts of blended learning, (T. Bosch); creation of a hybrid learning environment that allows students to use the advantages of electronic submission and preparation of reports on practical work (M. Amelung, D. Rösner); careful planning of online learning stages based on the didactic triangle (D. Petko); supporting the idea of a "flipped classroom" where classroom activities are used for interactive and collaborative, experiential, dialogic learning instead of teacher-centered knowledge dissemination (M. Brand, K. Mahlke); basing blended learning on the basis of video lectures developed by using a standardized solution for the entire educational institution (T. Hirmer, A. Henrich); creation of a hybrid campus based on multimodal learning (A. Skulmowski, G. D. Rey); chronological arrangement of the elements of the educational offer for the desired success in education (K. Keller, D. Klinkhammer, E.-M. Rottlaender).